Síntesis y caraterización del ligando tris-(2-tiosalicilamidoetil)amina y sus complejos de hierro e indio - Guerra García, Pedro Pablo (Universidad de Costa Rica, 2009)
The coordination chemistry of the hexadentate ligand, tris(2-thiosalicylamidoethyl)amine, (LH3), was studied. The reaction of the ligand trianion with iron(III) and indium(III) yields monomeric hexacoordinate complexes, LFe·HCl and LIn. The complexes were characterized by spectroscopic, magnetic and electrochemical methods.